Comparison of the effectiveness of participation in cognitive and metacognitive exercises on elementary students\' team working - hosainali tajikesmaeali (مجله علوم روانشناختی, 2023)
Background: Improving teamwork spirit is one of the most important goals of educational systems. On the other hand, cognitive and metacognitive strategies are recognized as one of the most practical techniques in educational methods. Despite the significance of enhancing teamwork spirit in students and the multifaceted emphasis in higher-level documents, there has been no study conducted to investigate the impact of cognitive and metacognitive strategies on students' teamwork spirit so far. Aims: The aim of the present research was to compare the effectiveness of cognitive and metacognitive strategies on elementary students' teamwork spirit. Methods: The current research employed a semi-experimental design of pre-test-post-test with a control group. The target population included all male elementary students in Malard County during the academic year 2022-2023. Using convenience sampling, 15 students were selected for each group, totaling 45 participants, and were randomly assigned to two experimental groups and one control group. To measure teamwork spirit, the Lencioni Team Assessment questionnaire (2004) was utilized. Additionally, an instructional protocol based on Saif's approach (2016) was implemented in 10 sessions, each lasting 60 minutes, for the students in the two experimental groups. The control group did not receive any specific intervention. Data analysis was conducted using SPSS version 26. Results: The findings in the current study demonstrated that the impact of both cognitive and metacognitive interventions was significant across all sub-scales of teamwork spirit (p < 0.05). Upon reviewing the calculated effect sizes, the results indicated the highest effect on the commitment component with an effect size of 0.87, followed by the accountability component with an effect size of 0.75. Conclusion: The comparison of the interventions indicated that the effectiveness of metacognitive strategies on teamwork spirit was significantly higher than cognitive strategies. Based on these results, it can be inferred that both metacognitive and cognitive interventions have the potential to enhance teamwork spirit in students. Professionals in the field of education, counselors, and school psychologists can utilize these interventions to improve students' teamwork spirit.